Faktor Penentu Keputusan Pembelian Online pada E-Commerce Shopee di Era Pasca Pandemi COVID-19: Studi Empiris di Kota Banda Aceh - Mufti, Muhammad Arif; Sari, Nilam; Zulhilmi, Muhammad (Journal of Law and Economics, 2024)
This study employs a quantitative approach, utilizing both primary and secondary data sources. The objective is to examine the influence of price, trust, and security on online purchasing decisions on Shopee e-commerce in the post-COVID-19 pandemic era. The population consists of residents of Banda Aceh City, with a sample of 100 respondents selected using the purposive sampling technique. Data analysis is conducted using multiple linear regression with the assistance of SPSS software. The findings indicate that the variables of price, trust, and security collectively have a positive and significant effect on purchasing decisions. Individually, each variable—price, trust, and security—also exerts a positive and significant influence on purchasing decisions.